In What Sense an Evolution of Metropolitan Planning Actors? - Şahin, Savaş Zafer; Galland, Daniel; Tewdwr-Jones, Mark (Springer, 2020)
This chapter addresses the changing roles of actors in metropolitan planning considering generations of metropolitan reforms where planning strategies and policies are shaped by agents with oftentimes conflicting conceptions and agendas about metropolitan planning. We identify and examine the transformation of key metropolitan planning actors in relation to fluctuating planning styles and assess the unintended consequences associated with changing power relations. We use illustrative examples from the West and Global South where ad hoc actors and constellations of actors shape metropolitan planning in different ways. The overall contribution is to provide a trajectory of the changing nature of influential actors and the interests that lie behind the redefinition and reinterpretation of metropolitan planning.
Keywords: Metropolregion; Planungsprozess; Akteur; Planungskonzept; Transformation; Planungssystem; Machtverteilung; Interessenlage; Einflussfaktor; Internationaler Vergleich; Agendasetzung